Osnove projektiranja konstrukcij: Zbirka vaj - Kozem Šilih, Erika; Držečnik, Mateja (University of Maribor Press, 2023)
Basis of Structural Design: Exercise Book. The " Basis of Structural Design - Exercise Book " is intended for students of civil engineering, transportation engineering and architecture. The complete set of exercises is based on European standards and focuses on the most important aspects of structural design. The publication includes explanations and solved examples in accordance with standards such as SIST EN 1990:2004, SIST EN 1991-1-1:2004, SIST-EN 1991-1-3:2004, SIST-EN 1991-1-4:2004, and SIST-EN 1998-1 2005. These exercises are intended to provide an understanding of the basic concepts of structural design, load analysis, and earthquake engineering that are essential to understanding the behaviour of structures. For further clarification and theoretical explanation of the solved examples, the authors refer the reader to the textbook " Basis of Structural Design." The authors hope that this collection of practise problems will be useful to students in their education to deepen their knowledge of structural design and serve as a guide for successful study and future work in civil engineering.